An empirical study on the ethics and motivating values of law students in Malaysia - Wu, Richard; Zul Kepli, Mohd Yazid (International Journal of Business, Economics and Law - IJBEL, 2019)
This article investigates the ethics and motivating values of law students in Malaysia in the final two years of their legal education. Our empirical research examines the demographics of these law students. This is followed by an examination on their responses to diverse ethical dilemmas including conflict of interest, bribery, corruption, and pro bono. The findings reveal that Malaysian law students are strongly inclined to obey to the law and will only give priority to family members’ well-being and family loyalty in extreme situations. The study suggests a relatively weak pro bono culture of Malaysian law students similar to their counterparts in Hong Kong. It was also discovered that an overwhelming number of respondents are not willing to sacrifice family time for their careers. The interest of family remains a strong consideration in making decision.